Religion out loud : religious sound, public space, and American pluralism - Weiner, Isaac (North American religions., 2013)
For six months in 2004, controversy raged in Hamtramck, Michigan, as residents debated a proposed amendment that would exempt the adhan, or Islamic call to prayer, from the city's anti-noise ordinance. The call to prayer functioned as a flashpoint in disputes about the integration of Muslims into this historically Polish-Catholic community. No one openly contested Muslims' right to worship in their mosques, but many neighbors framed their resistance around what they regarded as the inappropriate public pronouncement of Islamic presence, an announcement that audibly intruded upon their public s.